Corrigendum to "Dark tourism, abjection and blood: A festival context" [Tourism Management 64 (2018) 346–356]. (February 2019) - Podoshen, Jeffrey S.; Yan, Grace; Andrzejewski, Susan A.; Wallin, Jason; Venkatesh, Vivek
Abstract: Dark tourism and its implications have been gaining significant prominence in both the literature and in practice in recent years. Moving conceptualizations of dark tourism forward, we utilize the interpretative phenomenological frame to investigate the interrelationships between tourism and current conditions of society. We do this by qualitatively studying tourists' experiences while in the process of attending dark tourism oriented music festivals that prominently feature direct confrontation with abjection. Our findings indicate that these abjection-oriented festivals allow tourists to encounter blood, animal corpses and other death elements in a ritual-like context within the confines of a transitory space. Ultimately, our research reveals how dark tourism festivals featuring abjection can allow some tourists to feel closer to actual death.